Unearthing Positive Politeness Strategy in Commissive Illocutionary Acts - Ismi H, Saskia; Adriana, Vanessa; Ramadhanti, Rizka; Alyaa Ramadhani, Ratu; Zuraida Supri, Ida (International Journal of Psychosocial Rehabilitation, 2020)
This research aims at investigating the factors influencing the use of positive politeness strategy, identifying types of commissive illocutionary acts and analyzing the strategy used in delivering commissive illocutionary acts employed by the characters in a novel entitled Wildwood. The method used in this research is qualitative descriptive analysis, where the data is collected, then sorted and categorized and finally analyzed based on the theory. The results show that 1) the factors influencing to conduct positive politeness strategy is the payoff and size of imposition factors, 2) Types of commissive illocutionary acts found are promise, threat, contract, swear, dan pledge, and 3) Both strategies are employed in delivering the commissive illocutionary acts; direct strategies is more dominant than the indirect one.